2010
DOI: 10.1038/bmt.2009.362
|View full text |Cite
|
Sign up to set email alerts
|

MTX or mycophenolate mofetil with CsA as GVHD prophylaxis after reduced-intensity conditioning PBSCT from HLA-identical siblings

Abstract: Mycophenolate mofetil (MMF) in combination with CsA seems to lead to earlier post transplant hematological recovery and less mucositis than MTX, with a similar incidence of GVHD. In this study we analyzed the post transplant outcomes of two cohorts of patients who underwent an HLA-identical sibling reduced intensity conditioning transplantation (allo-RIC) with GVHD prophylaxis consisting of CsA in combination with either MMF or a short course of MTX. We included 145 consecutive allo-RIC transplants performed b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
45
3
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(53 citation statements)
references
References 36 publications
4
45
3
1
Order By: Relevance
“…[31][32][33][34][35][36] and despite first-line prophylaxis usually consisting of CsA and MTX, GvHD still occurs in 10-50% of patients depending on the HLA disparity between host and donor. 29,52 Although CsA is considered a cornerstone in GvHD prophylaxis, we showed that its reduction of GvHD-related mortality was comparable to that observed by IVIG in our model. In a clinical setting, IVIG are used with CsA and other immunosuppressive drugs, although in our model IVIG and CsA were used alone.…”
Section: Discussionsupporting
confidence: 48%
“…[31][32][33][34][35][36] and despite first-line prophylaxis usually consisting of CsA and MTX, GvHD still occurs in 10-50% of patients depending on the HLA disparity between host and donor. 29,52 Although CsA is considered a cornerstone in GvHD prophylaxis, we showed that its reduction of GvHD-related mortality was comparable to that observed by IVIG in our model. In a clinical setting, IVIG are used with CsA and other immunosuppressive drugs, although in our model IVIG and CsA were used alone.…”
Section: Discussionsupporting
confidence: 48%
“…The type and dose of post-transplant immunosuppression in the context of non-ATG-containing, fludarabinebased RIC from HLA-identical sibling donors was recently evaluated by Piñana et al 18 The authors found similar posttransplant outcomes with either a combination of CsA and MTX or of CsA and MMF. In our study, we also observed similar outcomes in the group of patients who received MTX or MMF and CsA without ATG (data not shown), but this group had a higher risk of chronic GVHD leading to worse survivals.…”
Section: N Lfs Os Ri Nrmmentioning
confidence: 88%
“…Transplantation outcomes were similar in the two groups with the exception of a higher incidence of grade 2-4 mucositis with CsA + MTX. 18 In this study, we retrospectively investigated the impact of the intensity of the GVHD prophylaxis on the posttransplant outcomes of a homogeneous cohort of 228 adult patients over 50 years old with de novo acute myeloid leukemia in first complete remission given haematopoietic stem cells from HLA-identical siblings following fludarabine and 2 days of intravenous busulfan (Flu-ivBu2) RIC. We analyzed the impact of the use of ATG with CsA compared to a combination of ATG and CsA + MTX or MMF versus CsA and MTX or MMF with no ATG as post-transplant GVHD prophylaxis.…”
Section: ©2015 Ferrata Storti Foundation This Is An Open-access Papementioning
confidence: 99%
“…These include use of immunosuppressive drugs singly and in combination [14,15], tailoring the dose of CsA depending on blood levels [16,17] and evaluation of newer immunosuppressive agents in comparison with standard agents [5][6][7][8][9][10]. CsA combined with either MTX or MMF is the most widely used immunosuppressive drug [5,6,8].…”
Section: Discussionmentioning
confidence: 99%
“…Mycophenolate mofetil (MMF), a pro-drug of mycophenolic acid, inhibit T cell activation and proliferation and has been used in combination with CsA for GVHD prophylaxis [8][9][10]. Compared to MTX, MMF has been shown to be less toxic when used in combination with CsA for GVHD prophylaxis [8].…”
Section: Introductionmentioning
confidence: 99%